Daya Racun Ekstraktif Kulit Kayu Pucung terhadap Rayap Kayu Kering Cryptotermes cynocephalus Light. Toxicity of Pucung-wood Bark Extractives to Dry Wood Termite Cryptotermes cynocephalus Light - Laila Sari; Sutjipto A. Hadikusumo (Jurnal Ilmu dan Teknologi Kayu Tropis, 2004)
Wood preservation using chemicals may pollute the environment. One of the efforts to reduce the effect is using naturally constituents from plants as preservative. The purpose of this study was to observe the effectiveness of soluble fraction in n-hexane, diethyl ether and ethyl acetate of pucung-wood bark after extracted in acetone to dry wood termite attack on paper disc. Pucung-wood (Pangium edule Reinw.) barks were dried and powdered and then cold-extracted with acetone. Thick extract solution in acetone was extracted in n-hexane solution. Soluble fraction in n-hexane was separated. Remained solution was extracted in diethyl ether. Soluble fraction was separated. Remained solution was extracted in ethyl acetate. Soluble fraction in ethyl acetate was separated. Each of soluble fractions was separated from the solution using evaporation method to obtain dry extracts. Each dry extracts were dissolved in each solution to make solutions with concentration of 2.5%, 5%, 7.5% and 10%. Filter paper was used as sample and soaked in the extract solution for 24 hours. After air-dried, filter paper was placed on petri dish and feed to 50 dry termites for 4 weeks. Results shown that 2.5% extract solution in n-hexane or in ethyl ether, or 5% in acetone or 10% in ethyl acetate were effectively inhibiting dry wood termite attack with mortality of 95 ~ 100%.